Genetic progress of 18 years of a soybean breeding program for the Brazilian Central-West - Henrique Ribeiro de Campos, Luis; Diego Silva Cabral, Pablo; Higino de Lima e Silva, Fernando; Castoldi, Gustavo; Pereira Marques, Renata (Revista Ciência Agronômica, 2023)
In a breeding program, the estimation of genetic progress over the years provides a broad view of the program as well as grounds for optimal decision-making. In this respect, the present study proposes to estimate the genetic progress of 54 soybean cultivars released to the Brazilian Midwest between the years 2000 and 2017. Two experiments were conducted during the 2017/18 crop year. Grain yield (GY), maturity group (MG), 100-seed weight (100SW), number of pods per plant (NPP), number of seeds per pod (NSP) and plant height (PH) were evaluated. Genetic progress was estimated by the direct methodology and by linear regression. According to the direct method, the average annual genetic progress was positive for GY (1.92%), 100SW (2.69%), NPP (2.31%), NSP (1.10%) and PH (0.32%), but negative for MG (-0.44%). The results obtained using both methodologies agree on the obtained increases for GY and 100SW and the decreases for MG.